2014
DOI: 10.1073/pnas.1404396111
|View full text |Cite
|
Sign up to set email alerts
|

Memory reactivation during rest supports upcoming learning of related content

Abstract: Although a number of studies have highlighted the importance of offline processes for memory, how these mechanisms influence future learning remains unknown. Participants with established memories for a set of initial face-object associations were scanned during passive rest and during encoding of new related and unrelated pairs of objects. Spontaneous reactivation of established memories and enhanced hippocampal-neocortical functional connectivity during rest was related to better subsequent learning, specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
139
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(158 citation statements)
references
References 35 publications
16
139
3
Order By: Relevance
“…Previous studies in humans have demonstrated that post-learning reactivation events can be observed via multivariate pattern analyses on fMRI data (Deuker et al, 2013; Schlichting and Preston, 2014; Staresina et al, 2013). These studies have reported reactivation of specific items or item categories in entorhinal, retrosplenial, (Staresina et al (2013), and occipitotemporal cortex (Deuker et al, 2013; Schlichting and Preston, 2014), but reactivation has not been observed in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies in humans have demonstrated that post-learning reactivation events can be observed via multivariate pattern analyses on fMRI data (Deuker et al, 2013; Schlichting and Preston, 2014; Staresina et al, 2013). These studies have reported reactivation of specific items or item categories in entorhinal, retrosplenial, (Staresina et al (2013), and occipitotemporal cortex (Deuker et al, 2013; Schlichting and Preston, 2014), but reactivation has not been observed in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have reported reactivation of specific items or item categories in entorhinal, retrosplenial, (Staresina et al (2013), and occipitotemporal cortex (Deuker et al, 2013; Schlichting and Preston, 2014), but reactivation has not been observed in the hippocampus. In contrast, single-unit recording studies have only demonstrated hippocampal replay of spatial context information, with the strongest effects for place cell sequences associated with rewards.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the established functional differences in lateral versus medial subregions of entorhinal cortex (ERC; e.g., Knierim et al, 2014) and the limited resolution of fMRI, we excluded ERC from our analyses. The segmentations were validated by two other expert raters and have been used in previous published studies (Schlichting and Preston, 2014; Schlichting et al, 2015). PRC was defined as the lateral and medial wall of the collateral sulcus and a 3mm wide transition zone between PHC and PRC was excluded from both regions.…”
Section: Methodsmentioning
confidence: 99%
“…7 Episodic memories are gradually assimilated into longterm memory and this process is strongly influenced by sleep & existing memories are spontaneously reactivated and strengthened in the brain during rest periods. 8,9 Sleep problems and sleep deprivation lead to poor academic performance and excessive day time sleepiness in college students. 10,11 Since medical students are required to be alert & attentive during learning period so that they acquire professional level knowledge & skills of patient care, medical students who already have lots of academic burden and sleep problems due to other factors, smartphone overuse/addiction if present may further complicate the things and may lead to significant stress & mental health problems.…”
mentioning
confidence: 99%